High‐Index Faceted PdPtCu Ultrathin Nanorings Enable Highly Active and Stable Oxygen Reduction Electrocatalysis. Issue 6 (12th May 2021) - Li, Menggang; Tian, Fenyang; Lin, Tianshu; Tao, Lu; Guo, Xin; Chao, Yuguang; Guo, Ziqi; Zhang, Qinghua; Gu, Lin; Yang, Weiwei; Yu, Yongsheng; Guo, Shaojun
Abstract: Ultrathin nanosheet catalysts deliver great potential in catalyzing the oxygen reduction reaction (ORR), but encounter the ceiling of the surface atomic utilizations, thus presenting a challenge associated with further boosting catalytic activity. Herein, a kind of PdPtCu ultrathin nanorings with increased numbers of electrocatalytically active sites is reported, with the purpose of breaking the activity ceiling of conventional catalysts. The as‐made PdPtCu nanorings possess abundant high‐index facets at the edge of both the exterior and interior surfaces. An ultrahigh electrochemical active surface area of 92.2 m 2 g –1 PGM is achieved on this novel catalyst, much higher than that of the commercial Pt/C catalyst. The optimized Pd39 Pt33 Cu28 /C shows a great enhanced ORR activity with a specific activity of 2.39 mA cm –2 and a mass activity of 1.97 A mg –1 PGM at 0.9 V (versus RHE), as well as superior durability within 30 000 cycles. Density function theory calculations reveal that the high‐index facets and alloying Cu atoms can optimize the oxygen adsorption energy, explaining the enhanced ORR activity. Overcoming a key technical barrier in sub‐nanometer electrocatalysts, this work successfully introduces the hollow structures into the ultrathin nanosheets, heralding the exciting prospects of high‐performance ORR catalysts in fuel cells. Abstract : A kind of PdPtCu ultrathin nanorings with the surface dominated by the high‐index facets is reported to achieve a very high specific activity and mass activity toward oxygen reduction electrocatalysis. The enhanced activity is mainly originated from the optimized oxygen adsorption energy, which is caused by the combination of high‐index facets and the alloying effect of Cu.